Coupled Raman and FTIR Analysis of Biomass-Derived Carbon Prepared at Low Carbonization Temperature - Gugus Handika; Fairuz Gianirfan Nugroho; Afina Faza Hafiyyan; Feber Valentin Br Sembiring; Neysa Azzahra; Abu Saad Ansari; Nurul Taufiqu Rochman (Jurnal Riset Sains dan Kimia Terapan, 2026)
Biomass-derived carbon is commonly produced at high temperatures to promote graphitization; however, understanding carbon formation at lower temperatures remains critical for applications that rely on surface reactivity rather than crystallinity. In this work, carbon obtained from oil palm empty fruit bunch (EFB) through pyrolysis at 500 °C was systematically investigated using coupled Fourier transform infrared (FTIR) and Raman spectroscopy, supported by density functional theory (DFT)-based structural interpretation. FTIR analysis reveals extensive dehydration, cleavage of aliphatic C–H bonds, and progressive loss of oxygenated functional groups, accompanied by the emergence of aromatic C=C and C–O–C linkages. Raman spectra, resolved through pseudo-Voigt deconvolution, are dominated by defect-related bands (D, D2, D3, and D4) with a broadened G band, indicating the formation of small, disordered sp2 carbon domains rather than extended graphitic lattices. DFT-assisted analysis suggests that the carbon framework is composed of interconnected polyaromatic hydrocarbon clusters incorporating residual heteroatoms and mixed sp2–sp3bonding. These results demonstrate that low-temperature pyrolysis of EFB produces a defect-rich aromatic carbon structure strongly governed by precursor chemistry, offering a viable route for tailoring functional carbon materials with abundant active sites, making it highly suitable for applications in adsorption, catalysis, and environmental remediation technologies.